First record of Polycystididae (Platyhelminthes, Kalyptorhynchia) from Cuba, with the description of a new genus and five new species, and remarks and the description of one new species from Panama - Diez, Yander L.; Hernández, Claudia Sanjuan; Reygel, Patrick; Roosen, Paulien; Artois, Tom (Zootaxa, 2018)
The first records of Polycystididae from Cuba are provided and discussed. In total nine species have been collected, five of which are new to science, one representing a new genus. Polycydora intermedia gen. n. sp. n. shows intermediate features between Polycystis Kölliker, 1845 and Paulodora Marcus, 1948. The ovaries are kidney shaped, with the oocytes arranged in a row, and lack the hard “nozzles” of Paulodora. A female bursa as in Polycystis is present. In P. intermedia gen. n. sp. n. lacks the strong muscle bulb at the male bursa and the accessory glands type I in the male atrium, which are present in Polycystis. The male atrial organs include a prostate stylet type II connected to a free prostate vesicle type II. The four new species (Phonorhynchoides minor sp. n., Phonorhynchopsis capillaris sp. n., Phonorhynchopsis sublinguatus sp. n., Myobulla armenterosi sp. n.) are distinguished from their congeners by the specific shape and length of the male hard copulatory structures. Phonorhynchoides minor sp. n. has the smallest stylets within the genus, and these stylets are more straight than those of the other species of the genus. In Phonorhynchopsis capillaris sp. n. the prostate stylet type IV is only 20% of the length of the accessory stylet type IV, the lowest relative length within the genus. The accessory stylet in this species is extremely thin; it is only 2 µm wide. Phonorhynchopsis sublinguatus sp. n. has a prostate stylet widened in the distal half, ending in a rounded tip, not twisted in the middle. Because of its strong resemblance to M. armenterosi sp. n., M. berti sp. n., a new species of Myobulla Artois & Schockaert, 2000 collected at the Atlantic coast of Panama is described here too. Both species of Myobulla have a prostate stylet type III that shows a 90° turn at some point, as is the case in some other species of Myobulla. In M. berti sp. n. the stylet is smaller overall and is bent in the middle; in M. armenterosi sp. n. the stylet is larger and it is bent more distally. All of the four known species have a very wide geographical distribution: Phonorhynchopsis haegheni, Alcha evelinae, Paraustrorhynchus elixus, and Gyratrix hermaphroditus.